Study on the Implementation of Food Waste Management in the Pastry Department of The Westin Hotel Jakarta - Laurentsia, Angelica; Ardiansyah, Imam (Pusat Publikasi Nusantara, 2025)
This study aims to examine the implementation of food waste management practices in the pastry department of The Westin Jakarta Hotel by employing the food waste hierarchy framework, which encompasses five dimensions: prevention, reuse, recycling, recovery, and disposal. The research adopts an applied qualitative approach, utilizing data triangulation through observation, in-depth interviews, and document analysis. Key informants include the sous chef, chef de partie, and waste management staff. Data were analyzed using an interactive analysis model, which consists of data collection, data reduction, data display, and conclusion drawing. Findings indicate that, within the prevention dimension, production planning based on forecasting, along with the implementation of FIFO (First In, First Out) and FEFO (First Expired, First Out) systems, has proven effective in minimizing raw material waste. In the reuse dimension, efforts to repurpose leftover dough and unsold products have been implemented, although on a limited scale. For the recycling dimension, used cooking oil from pastry production is collected and handed over to relevant parties for further processing. The recovery dimension is reflected in the use of leftover pastry products as feed for maggots, albeit still at a small scale, while used oil is sold to an external partner for conversion into biodiesel. Waste disposal is carried out through the separation of organic and inorganic waste, in collaboration with third-party service providers to ensure environmentally responsible waste management. Overall, while a range of positive practices have been adopted, improvements are needed in technological integration and the establishment of more efficient partnerships to better support hotel operations and environmental sustainability.